If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(y + 3) + 2 = 2y + 8 Reorder the terms: 6(3 + y) + 2 = 2y + 8 (3 * 6 + y * 6) + 2 = 2y + 8 (18 + 6y) + 2 = 2y + 8 Reorder the terms: 18 + 2 + 6y = 2y + 8 Combine like terms: 18 + 2 = 20 20 + 6y = 2y + 8 Reorder the terms: 20 + 6y = 8 + 2y Solving 20 + 6y = 8 + 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. 20 + 6y + -2y = 8 + 2y + -2y Combine like terms: 6y + -2y = 4y 20 + 4y = 8 + 2y + -2y Combine like terms: 2y + -2y = 0 20 + 4y = 8 + 0 20 + 4y = 8 Add '-20' to each side of the equation. 20 + -20 + 4y = 8 + -20 Combine like terms: 20 + -20 = 0 0 + 4y = 8 + -20 4y = 8 + -20 Combine like terms: 8 + -20 = -12 4y = -12 Divide each side by '4'. y = -3 Simplifying y = -3
| [6w-2]=[6w+18] | | in(4x)=1 | | 2+3(3e+2)-4=-10 | | 2x^3-2x^2-32x+40=0 | | x+42=36 | | 2x(x-12)=0 | | 10X+5=9X+7 | | 8h-27=37 | | x^3-19x-6=0 | | 100-7=93 | | 12u^2+2U= | | 14a^2+9a-207=0 | | 14a^2+9a^2-207a=0 | | 4x+5=3(x+1) | | 10x+2=2x+50 | | 3(x-6)=27 | | 2x-8x-4=8x+6-7+4 | | (-17-2x)(10+3x)=0 | | 6a-9a=4 | | 9=2c-6 | | 3x+5a+8b=4b-8a+7x | | lg(x)+lg(2)=3 | | [2t+3]=[2t+-4] | | [2t+3]=[2+-4] | | Ln^2x-4lnx-5=0 | | 2x+3a-4b=-2b-11x+9a | | -30+2P=70-2P | | 2a+4=0.5a-0.25 | | 39a+39=20a-68 | | 2(3m+1)+16=6(2m-3) | | [5y+1]=[13y-7] | | 4(w+3)=27 |